Impact of soil moisture dynamics on yield of intercrops andnatural gum exudation in rainfed agroforestry system in semi-arid region - Prasad, Rajendra; Arunachalam, Ayyanadar; Alam, Badre; Handa, Arun Kumar; Ram, Asha; Singh, Ramesh; Shukla, Ashok; Singh, Prashant (Indian Journal of Agroforestry, 2025)
The present investigation was carried out in a seven-year-old agroforestry system based on two gum-yielding trees, Acacia nilotica and Acacia senegal, planted at three spacings (10×10 m, 10×5 m, and 5×5 m) under unirrigated (rainfed) conditions in the semi-arid region of Bundelkhand, Central India. The objective of the study was to assess how soil moisture dynamics across different tree spacings influence the yield of intercrops and natural gum exudation under rainfed semi-arid conditions. The study was conducted during 2019–2020, following a cropping sequence of sesame (Sesamum indicum L.) in kharif and taramira (Eruca sativa Mill.) in rabi. Soil moisture content was estimated gravimetrically each month throughout the year. Findings revealed that tree species, planting spacing or tree density, and months significantly influenced soil moisture dynamics in the 0–30 cm depth. Soil under A. senegal retained higher moisture compared to A. nilotica. Closer spacing (5×5 m) maintained higher soil moisture than wider spacings (10×5 and 10×10 m). Rainy-season months recorded higher soil moisture than winter and summer. Maximum soil moisture was observed in A. senegal at 5×5 m in October (82.58 mm), while the minimum occurred in A. nilotica at 10×10 m in April (9.39 mm). Incremental growth in GBH, height, and canopy spread varied with spacing. The yield of both intercrops remained unaffected by tree species but was significantly influenced by spacing, with maximum yield at 10×10 m and minimum at 5×5 m. Both tree species naturally exuded gum during summer (May–June). A. senegal produced higher mean gum yield (33.2 g/tree) than A. nilotica (12.6 g/tree), and both species recorded maximum gum yield at 5×5 m spacing. Moisture content showed positive but weak correlations with tree growth, intercrop yield, and gum exudation. Gum yield was positively correlated with incremental tree growth. Overall, good soil moisture from adequate monsoon rainfall is likely to enhance tree growth, intercrop yield, and gum exudation, and spacing of 10×5 m is recommended for optimum resource use in semi-arid agroforestry systems involving A. nilotica and A. senegal.